2015
DOI: 10.1186/s12937-015-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

A review and meta-analysis of prospective studies of red and processed meat, meat cooking methods, heme iron, heterocyclic amines and prostate cancer

Abstract: Prostate cancer remains a significant public health concern among men in the U.S. and worldwide. Epidemiologic studies have generally produced inconclusive results for dietary risk factors for prostate cancer, including consumption of red and processed meats. We aimed to update a previous meta-analysis of prospective cohorts of red and processed meats and prostate cancer with the inclusion of new and updated cohort studies, as well as evaluate meat cooking methods, heme iron, and heterocyclic amine (HCA) intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 58 publications
1
57
1
2
Order By: Relevance
“…These observations underscore the importance of evaluating prostate tumour sub‐types in studies of lifestyle factors and prostate cancer risk: men with healthier behaviours may potentially participate more in prostate cancer screening and may be more likely to be diagnosed with forms of low‐grade prostate cancer, hence obscuring any possible association. We did not find a significant association between body fatness and prostate cancer; our results indicate that meeting the specific recommendations on plant foods and animal foods was associated to lower risk of undifferentiated prostate cancer; however these observations are not supported by the current literature …”
Section: Discussioncontrasting
confidence: 97%
“…These observations underscore the importance of evaluating prostate tumour sub‐types in studies of lifestyle factors and prostate cancer risk: men with healthier behaviours may potentially participate more in prostate cancer screening and may be more likely to be diagnosed with forms of low‐grade prostate cancer, hence obscuring any possible association. We did not find a significant association between body fatness and prostate cancer; our results indicate that meeting the specific recommendations on plant foods and animal foods was associated to lower risk of undifferentiated prostate cancer; however these observations are not supported by the current literature …”
Section: Discussioncontrasting
confidence: 97%
“…showed increased breast density in pre‐menopausal women associated with high consumption of red meat. In 2014, the World Cancer Research Fund and the American Institute for Cancer Research (WCRF/AICR) observed null results for their meta‐analyses of the associations between red and processed meat and prostate cancer risk, consistent with a meta‐analysis published in 2015 . In contrast, in a pooled analysis of 15 cohort studies published in 2016, Wu et al .…”
mentioning
confidence: 65%
“…Regarding prostate cancer, our null result is consistent with two large and recent meta‐analyses of prospective studies, performed by the WCRF/AICR in 2014 18 and Blysma et al . in 2015 . In a pooled analysis of 15 cohort studies, Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogenic activity of meat may be mediated by the presence of mutagenic compounds; such as heterocyclic amines and polycyclic aromatic hydrocarbons, which are formed during cooking at high temperatures or over flame. However, a recent meta-analysis failed to show any positive correlation between red and processed meat, cooking methods, and the concentration of heterocyclic amines with the risk of PC [49]. This observation suggests that the Western dietary pattern may have more complex interactions with PC risk than those expected for the red meat and processed meat considered as individual foods.…”
Section: Discussionmentioning
confidence: 99%